Pola Komunikasi Dakwah dalam Meningkatkan Kepercayaan Diri Santri - Kiya Imania Azkiya Mukhlisa; Imania Azkiya Mukhlisa (Bandung Conference Series: Islamic Broadcast Communication, 2022)
Abstract. The da'wah training activity which is part of plkj activities aims to train students mentally so that they can be confident when speaking in public, especially when delivering speeches, lectures and sermons accompanied by community social activities. The purpose and benefits of this study are to find out the level of self-confidence of students before and after participating in PLKJ activities, to find out how much influence communication patterns have in increasing student self-confidence and find out how much influence PLKJ has on the development of student potential. The research method used is a qualitative descriptive method using interview data collection techniques, literacy and documentationThis type of research is qualitative with a descriptive case study approach. The selection of informants in this study used a purposive sampling technique and data collection techniques by observation, interviews, and documentation. The results of this study are grade XII students of Exactly 80 Sindangkasih for the Academic Year 2021/2022 have a strong enthusiasm for activities PLKJ. In addition to being an obligation for prospective alumni, PLKJ activities have many positive impacts on the development of students' potential, skills and social. The activities and debriefing of PLKJ, it helps students to be more confident in increasing their potential and increasing their social spirit. In addition, PLKJ activities provide many new experiences and insights so that students are much more open-minded. The supporting factors that support this activity are the spirit of proselytizing, the community environment and comrades-in-arms, factors hindering inadequate facilities and less strategic location. As for suggestions from the author, use the inhibiting factor as an evaluation in terms of choosing a more adequate and strategic location so that students can be more optimal in supporting all work program activities that have been systematically arranged. Abstrak. Kegiatan training dakwah yang merupakan bagian dari kegiatan PLKJ bertujuan untuk melatih mental siswa sehingga bisa percaya diri ketika berbicara di depan umum ketika menyampaikan pidato, ceramah dan khutbah yang disertai dengan kegiatan sosial masyarakat. Adapun tujuan dan manfaat penelitian ini adalah mengetahui tingkat kepercayaan diri santri sebelum dan sesudah mengikuti kegiatan PLKJ, untuk mengetahui pengaruh pola komunikasi dalam meningkatkan kepercayaan diri siswa dan untuk mengetahui seberapa besar pengaruh PLKJ terhadap perkembangan potensi siswa. Metode penelitian yang digunakan adalah metode deskriptif kualitatif dengan menggunakan teknik pengumpulan data observasi, wawancara, literasi dan dokumentasi. Hasil dari penelitian ini yaitu siswa kelas XII Madrasah Aliyah Persis 80 Sindangkasih Tahun Ajaran 2021/2022 memiliki antusias yang timggi terhadap kegiatan PLKJ. Selain menjadi kewajiban untuk para calon alumni, kegiatan PLKJ memberikan banyak dampak positif terhadap perkembangan potensi, skill dan sosial siswa. Dengan adanya kegiatan dan pembekalan PLKJ membantu siswa sehingga lebih percaya diri dalam meningkatkan potensi yang dimiliki serta meningkatkan jiwa sosial. Selain itu, kegiatan PLKJ banyak memberikan ilmu, pengalaman dan wawasan sehingga siswa jauh lebih open minded. Adapun faktor pendukung kegiatan ini yaitu semangat dakwah, lingkungan masyarakat dan kawan seperjuangan lalu faktor penghambatnya fasilitas yang kurang memadai dan lokasi tempat yang kurang strategis. Untuk saran yang penulis berikan, gunakan faktor penghambat sebagai bahan penilaian dalam hal pemilihan lokasi yang lebih cocok dan strategis agar mahasiswa dapat lebih optimal dalam mendukung seluruh kegiatan program kerja yang telah disusun secara sistematis